Structure and charge transfer processes at the Pt(111)/solid polymer electrolyte interface: a mesoscopic approach (2014)
Abstract: Modified electrodes are a very active area of electrochemistry, with multiple and widespread uses. They are a central component in many electrochemical devices, in which usually a thin membrane covers the electrode, as in Proton Exchange Fuel cells. Thus, understanding the structure and molecular processes at electrode/membrane interfaces constitutes an important issue for an efficient development of these devices. In this work, Nafion® coated Pt(111) electrodes were studied and experimental results were explained in light of two different theoretical approaches. Initially, the structure and dynamics of the electrode/SPE interface was described in terms of the acid/base equilibrium and the different mobility of membrane ionic groups. Later, the reaction kinetics of a fundamental electrochemical surface reaction, such as the CO oxidation, was analyzed on basis of the effect of the adsorbed species segregation induced by the membrane’s two-phase nature. Results showed a strong interaction between Pt(111)and Nafion® membrane, giving rise to a preferential orientation, electric field driven, of polymer hydrophilic regions. The membrane apparently introduces a new charge transfer process, pH-dependent, around 0.50 V in the cyclic voltammogram (CV). However, the lack of a wavenumber blue-shift of both protonated and dissociated Nafion®’s sulfonic groups with increasing the electrode potential would suggest that sulfonate anions are not specifically adsorbed but populate the double layer (DL). In agreement, proposed model predicts local maxima and minima in the capacitance, as consequence of either the change in the total interaction energy experienced by an ion inside the membrane with the applied potential or the acid/base dissociation process and the different ion mobility inside the membrane. The model extends the conceptual framework for the interpretation of CVs for these systems and the general theory for electrified interfaces. Additionally, it provides a tool towards the understanding of the electrocatalytic activity on modified electrodes. In general, the membrane close to the electrode surface may inhibit the electron transfer rate (ETR) of electrochemical reactions that strongly depend on the structure of the DL, well because blocks surface sites or because of the smaller potential drop at the Outer Helmholtz Plane. However, in some cases, the ETR can be enhanced. Experimentally, hydrogen and OH adsorption/desorption regions on Nafion® coated electrodes are significantly blocked, probably because a fraction of the Pt(111) surface is covered by the membrane backbone and becomes electrochemically inactive. Additionally, CO stripping experiments revealed a modification on the CO-adlayer structure and a slower reaction rate, which occurs in a sharper peak, and shifted to higher potential values, than on bare Pt (111) electrodes. Mean Field Approximate theory and Dynamic Monte Carlo Simulations suggest that Nafion® membrane modifies the “effective” interactions between adsorbed molecules: CO ads, OH ads and water, turning them into a more “attractive” character than in the case of a bare electrode and so, promoting surface segregation.